The Function of Local Government in Public Policy Evaluation Networked Modern Stores in Banjarmasin City - Firdaus, Muhammad Riyandi; Suaedi, Falih; Wardiyanto, Bintoro (Journal of Local Government Issues, 2023)
The presence of modern networked stores in the city of Banjarmasin causes traditional business actors to feel marginalized. The distance between establishments is such close operational times that are not following regulations, as well as partnerships and discourses on a moratorium on the establishment, are the causes of the underlying policies that have not run optimally. The purpose of this study is to explore and analyze policy evaluation through the role of actors, especially the Government, in protecting the existence of small-scale business actors behind the strong capitalist economic flows represented by modern networked stores. Indicators of the role of policies become new knowledge spaces in policy evaluation studies that will provide practical benefits for the Government in seeing the natural policy conditions behind the evaluation process, which is often carried out in formal conditions. This study uses a case study method with a qualitative research approach. The results show that policy evaluation is still not effective though the Regional Government as a critical actor has played its role in maintaining policy consistency so that competition between large investors represented through modern networked shops and small investors represented by micro, small and medium enterprises, and traders runs healthily. This paper argues that a consistent public policy will impact achieving the goals and objectives of the policy, only that an economic system based on capital, motives, and interests is another factor that influences the course of a evaluation public policy.